Efficacy ofGnRH and PGF2alpha in augmenting the reproductive performance of postpartum cows - SHESHAPPA, H; HONNAPPAGOL, S S; DHABALE, R B; TANDLE, M K (The Indian Journal of Animal Reproduction, 2023)
The post-partum GnRH-PGFp. honnonal therapy employed in the present study resulted in enhanced post-partum reproductive performance in terms of early involution of uterus and exhibition of first postpartum estrus